(untitled) (CAHIERS MAGELLANES-NS, 2024)
Slums are considered one of the foremost problems suffered by developed countries as well as developing countries, and due to the expansion of this phenomenon and its repercussions in recent years in Iraq in general and in Baghdad in particular, it has become necessary to address this phenomenon and provide effective solutions to what exists on the ground and limit its spread, especially after - The United Nations Millennium Development Goals, which emerged in 2000, were issued, where Goal 7-11 called for the necessity of achieving a significant improvement in the living conditions of more than 100 million people living in slums (slums) by 2020. - The Iraqi Council of Ministers issued Decision No. 320 of 2020, which granted all trespassers on government agricultural lands (which do not conflict with public interests and public services The Council of Ministers issued Resolution No. 286 of 2022 regarding the engineering and service effort team to introduce services to the encroachment areas. This resolution was the nucleus for providing services to these areas and finding housing solutions.